GAMBARAN PERILAKU PROSOSIAL RELAWAN DI RUMAH ORANG DENGAN GANGGUAN JIWA YAYASAN HIRO HUMANITY - Anggun Dwitika (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe the prosocial behavior of volunteers in assisting people with mental disorders (ODGJ) at Hiro Humanity Foundation and identify the factors influencing the emergence of such behavior. This research employed a qualitative approach with a phenomenological design. Data collection was conducted through interviews and observations involving three volunteers at Hiro Humanity as research informants. Data analysis used Interpretative Phenomenological Analysis (IPA). The findings showed that volunteers demonstrated prosocial behavior through voluntary assistance, emotional support, providing safety and comfort, as well as physical and material assistance during patient rehabilitation. Volunteers also actively participated in planning and implementing rehabilitation activities for patients. Factors influencing prosocial behavior included empathy, internal motivation, self-development, peer influence, and experiences gained during the mentoring process. The study highlights that prosocial behavior among volunteers contributes significantly to supporting the psychological recovery and social functioning of ODGJ patients.